Consulting report – servicios call center del Perú s.a. improvement of the management model of the Oncosalud platform - Montesinos Cuadros, Daniela Valeria (Pontificia Universidad Católica del Perú, 2018)
Servicios Call Center del Perú’s major external market client, Oncosalud, accounts for up to nine percent of the company’s total revenues and is thus a strategic partner. This consultancy project focuses on generating an effective and sustainable solution to the decrease in the sales per hour and lead conversion rates of the outbound cancer insurance sales services Oncosalud hires from SCC. After a thorough assessment, it was noted that an overall inefficient platform management led to the poor performance in the last few months. The proposed solutions have been classified in two components: People and Procedures. The People component refers to attaining the most suitable environment for the right people involved in the sale process and also, to create a team-based and teamwork structure in the platform. On the other hand, Procedures, addresses the way platform members interact and professionally support with each other. Extensive specialized literature provides evidence, authenticates, and supports the specific conditions in which these sorts of the proposed solution and derived activities must occur. For this reason, the consultancy team has developed in-depth guidelines and specifications on the most appropriate methods to implement and augment the effectiveness of the expected outcomes that this report entails. Through the implementation of the solution developed in this consultancy project, the financial results of the platform would increase considerably. At the same time, under this model framework, the sales number will stabilize and provide a positive balance in the platform financial reports. Moreover, the people management system proposed allows revenues and cost reduction improvements in the short-term and will help to create a superior working and service providing environment that will be of help to the company’s financial performance in the Oncosalud platform as well as in other inbound or outbound platforms.

Oncosalud representa cerca del nueve por ciento de los ingresos totales de Servicios Call Center del Perú, esto lo convierte en un socio estratégico. Sin embargo, la disminución de la tasa de lead conversion y la tasa de ventas por hora de seguros oncológicos está poniendo en riesgo a la organización. Después de haber realizado una evaluación exhaustiva, se encontró que este bajo rendimiento, se debe a una gestión ineficiente de la plataforma. Por ello, el presente proyecto de consultoría se enfoca en generar una solución efectiva y sostenible ante este problema. Las soluciones propuestas se han clasificado en dos componentes: personas y procedimientos. El componente Personas se refiere a generar un entorno idóneo para las personas aptas que forman parte del proceso de ventas e implementar una estructura de equipos y trabajo colaborativo en la plataforma. Por otro lado, en Procedimientos, se aborda cómo los miembros de la plataforma interactúan entre sí y se apoyan profesionalmente. La extensa literatura especializada proporciona evidencia, valida y respalda las condiciones específicas requeridas maximizar el efecto de estas soluciones. Por esta razón, se han desarrollado pautas y especificaciones detalladas sobre los métodos más apropiados para implementar y aumentar la efectividad de los resultados esperados que este informe presenta. Mediante la implementación de la solución desarrollada en este proyecto, los resultados financieros de la plataforma aumentarán considerablemente. Al mismo tiempo, bajo este marco modelo, el número de ventas se estabilizará y proporcionará un balance positivo en los informes financieros de la plataforma. El sistema de gestión de personas propuesto permite además de mejorar los ingresos y reducir los costos en el corto plazo; crear un entorno de trabajo y servicio productivo que impactará en el desempeño financiero de la plataforma Oncosalud, así como de otras plataformas de SCC, ya sean inbound o outbound.
Keywords: Servicios de salud--Perú; Clínicas--Perú; Administración de servicios de salud--Perú.; https://purl.org/pe-repo/ocde/ford#5.02.04